x x*7
Применяем правило производной умножения:
ddx(f(x)g(x))=f(x)ddxg(x)+g(x)ddxf(x)\frac{d}{d x}\left(f{\left (x \right )} g{\left (x \right )}\right) = f{\left (x \right )} \frac{d}{d x} g{\left (x \right )} + g{\left (x \right )} \frac{d}{d x} f{\left (x \right )}dxd(f(x)g(x))=f(x)dxdg(x)+g(x)dxdf(x)
f(x)=xf{\left (x \right )} = xf(x)=x; найдём ddxf(x)\frac{d}{d x} f{\left (x \right )}dxdf(x):
В силу правила, применим: xxx получим 111
g(x)=7xg{\left (x \right )} = 7^{x}g(x)=7x; найдём ddxg(x)\frac{d}{d x} g{\left (x \right )}dxdg(x):
ddx7x=7xlog(7)\frac{d}{d x} 7^{x} = 7^{x} \log{\left (7 \right )}dxd7x=7xlog(7)
В результате: 7xxlog(7)+7x7^{x} x \log{\left (7 \right )} + 7^{x}7xxlog(7)+7x
Теперь упростим:
7x(xlog(7)+1)7^{x} \left(x \log{\left (7 \right )} + 1\right)7x(xlog(7)+1)
Ответ:
x x 7 + x*7 *log(7)
x 7 *(2 + x*log(7))*log(7)
x 2 7 *log (7)*(3 + x*log(7))